Seismic design and shake table tests of a steel post-tensioned self-centering moment frame with a slab accomodating frame expansion. - Chou, Chung-Che (Earthquake engineering & structural dynamics.)
Post-tensioned (PT) self-centering moment frames were developed as an alternative to welded moment-resisting frames (MRFs). Lateral deformation of a PT frame opens gaps between beams and columns. The use of a composite slab in welded MRFs limits the opening of gaps at the beam-to-column interfaces but cannot be adopted in PT self-centering frames. In this study, a sliding slab is used to minimize restraints to the expansion of the PT frame. A composite slab is rigidly connected to the beams in a single bay of the PT frame. A sliding device is installed between the floor beams and the beams in other bays, wherever the slab is allowed to slide. Many shaking table tests were conducted on a reduced-scale, two by two bay one-story specimen, which comprised one PT frame and two gravitational frames (GFs). The PT frame and GFs were self centering throughout the tests, responding in phase with only minor differences in peak drifts that were caused by the expansion of the PT frame. When the specimen was excited by the 1999 Chi-Chi earthquake with a peak ground acceleration of 1.87 g, the maximum interstory drift was 7.2 percent and the maximum lateral force was 270 kN, equal to 2.2 times the yield force of the specimen. Buckling of the beam bottom flange was observed near the column face, and the initial post-tensioning force in the columns and beams decreased by 50 and 22 percent, respectively. However, the specimen remained self-centering and its residual drift was 0.01 percent.